FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENDAPATAN USAHATANI KACANG HIJAU DI KELURAHAN RATONGAMOBO KECAMATAN BOAWAE KABUPATEN NAGEKEO - Bibiana Dafrosa Owa Nuwa; Sondang P Pudjiastuti; Lika Bernadina (Buletin Ilmiah Impas, 2020)
ABSTRACT The cultivation of green beans is a cultivation that cannot be separated in relation to income and factors that influence the yield of the cultivation of green beans. To achieve a maximum income, the factors used must be optimized. This research was conducted in Ratongamobo Village, Boawae Subdistrict, Nagekeo Regency, to find out 1) productivity level of the green bean farm, 2) the amount of income from the green bean farm, 3) the factors that influence the income of the green beans farm and 4 ) the size of the R/C ratio of growing green beans. The analysis method used is income analysis, Cobb- Douglass production function analysis and R/C ratio analysis. The results showed that the level of farm productivity in the research area was 1.33 tonnes/ha in one growing season. The average income of green bean farmers is Rp. Rp.6.051.441/ha, based on the results of multiple linear regression analyzes using the Cobb- Douglass function model, the factors that have a significant impact on income are land area at α 10%, while the factors such as seed costs, labor costs and fertilizer costs have no significant effect on the income. The value of the R/C ratio is known to be 2,10, which means that for each rupiah the costs incurred by farmers, will generate revenue of Rp. 2,10.